Saliva leptin levels in tooth movement during initial stage of orthodontic alignment: a pilot study - Abu Bakar, Noraini; Kamil, Wisam Alaa; Al-Bayati, Lina Hilal Abbood; Mustafa Al-Ahmad, Basma Ezzat (Piracicaba Dental School – UNICAMP, 2017)
INTRODUCTION During orthodontic tooth movement, the early response of periodontal tissues to mechanical stress is an acute inflammatory reaction. Mechanical stress from orthodontic appliances is believed to induce cells in the periodontal ligament (PDL) to form biologically active substances, such as enzymes and cytokines, responsible for connective tissue remodeling (Nishijima Y et al 2006). Leptin, a polypeptide hormone has been classified as a cytokine (Zhang et al 1994). Earlier findings concluded that leptin at high local concentrations protects the host from inflammation and infection as well as maintaining bone levels. It has been also suggested that leptin plays a significant role in bone formation by its direct effect on osteoblasts (Alparslan et al 2010). This pilot study aimed to study leptin in saliva and its association with tooth movement during initial orthodontic alignment.